MAP as a conservation method for contemporary art with foodstuffs : three case studies - Julie Gilman; Claire Van Damme; Bruno Demeulenaer; Frank Devlieghere (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article examines the use of Modified Atmosphere Packaging (MAP), a widely applied preservation method in the food packing industry, for preserving contemporary artworks with foodstuffs. Three case studies are presented for which guidelines to preserve those works are proposed, taking into account the temporal, ephemeral character of these artworks on the one hand and their material preservation on the other hand and to explore whether and how they can be presented and preserved for future generations.